Chomsky on State and Democracy - Grewendorf, Günther (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
According to the New York Times, Noam Chomsky is the most important intellectual of our time. He has not only revolutionised the theories of language and the human mind, but his concept of human nature has prompted him to fight for freedom and democracy and led to political analyses which concern the role of the state and the function of democracy (among others). The contributions to this book deal with the most important topics of his political work:human nature and the emergence of social institutionsthe relationship of the individual to the state and the gist of anarchismhuman rights and the notion of freedompower and resistanceWith contributions byRobert Barsky, Željko Bošković, Jean Bricmont, Günther Grewendorf, Georg Meggle, Milan Rai, Tom Roeper, Michael Schiffmann and Juan Uriagereka.